Effectiveness of remote dietary counseling intervention on cancer patients with enteral tube feeding undergoing chemotherapy - Linh, Nguyen Hoai; Lien, Nguyen Thi Hong; Ma, Duong Thi Huynh; My, Nguyen Thi Dieu; Chau, Phan Thi Ai (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
Background: Hue Central Hospital is a special-grade central - level hospital that has been and is promoting comprehensive patient care. The teamwork between treating physicians, nursing care, clinical pharmacists and nutritionists has initially shown positive patient treatment outcomes. Recognizing that cancer patients frequently enter and exit the hospital between chemotherapy cycles, remote nutritional counseling intervention is an effective measure to help patients adhere to a reasonable diet at home and prepare their physical condition for the next chemotherapy cycle. Therefore, we conducted this study to evaluate the effectiveness of remote nutritional counseling intervention on cancer patients with enteral feeding undergoing chemotherapy at the Oncology Center, Hue Central Hospital. Methods: A non - controlled interventional dietary study was conducted on 22 patients diagnosed with cancer and admitted for multiple chemotherapy cycles with enteral feeding indication at Hue Central Hospital Cancer Center from January to April 2024. Results: The nutritional status characteristics of the study subjects according to the clinical index Albumin < 25g/L accounted for 4.5%; BMI < 18.5 accounted for 27.3% and 90.9% of patients were assessed as malnourished according to PG-SGA. After nutritional intervention, most patients had positive changes in anthropometric and clinical parameters (p > 0.05). Conclusions: Remote home - based dietary intervention has demonstrated positive effects for patients.